Complexities of Genetic Counseling for ALS: A Case of Two Siblings with Discordant Genetic Test Results. Issue 4 (7th April 2015) - Mandich, Paola; Mantero, Vittorio; Verdiani, Simonetta; Gotta, Fabio; Caponnetto, Claudia; Bellone, Emilia; Ferrandes, Giovanna; Origone, Paola
Abstract: Rapid advances in the genetics of amyotrophic lateral sclerosis (ALS) have dramatically changed the approach of clinicians and researchers to the motor neuron diseases. We report two siblings in whom the genetic study provided conflicting results, hence raising a number of issues which deserve to be considered by clinicians involved in genetic testing for ALS. The first patient died within 2 years of ALS onset, while her brother still manages to walk unaided, 7 years into onset. Genetic analyses, performed on the first patient as part of a research protocol, and as clinical genetic testing on the brother, provided different results. Results for Patient 1 were negative for all investigated genes, thus suggesting that her disease may be a phenocopy, while her brother carried an autosomal dominant TARDBP mutation (p.A382T). A multidisciplinary approach may help patients and clinicians face the emerging dilemmas in such a complex field. Sharing and updating of advances, not to mention uncertainties inherent to current knowledge, with patients and families may prove to be an effective way to support them and to make them aware of the present limits of our knowledge and of the blurred border between research and clinical practice.